Business Feasibility Analysis for Investors in Telecommunications Companies for 2017-2022 Period Using the Financial Distress Model - Wijaya, John Henry; Denny Saputera,; Wahyu Panji Nugraha, (Technium Business and Management, 2024)
This study analyzes the financial viability of Indonesian telecommunications companies from 2017 to 2022 using financial distress models. The research focuses on comparing the Altman Z-Score and Grover models to predict financial distress, evaluating their effectiveness in providing insights for investors. The telecommunications sector in Indonesia has seen rapid growth, driven by increased smartphone penetration, internet access, and the adoption of 5G technology. However, this growth is accompanied by challenges such as intense competition, economic instability, and regulatory changes, which pose risks of financial distress.Financial distress in telecommunications companies is assessed through key financial ratios, examining liquidity, leverage, and profitability. The study utilizes historical financial data from leading telecommunications companies, applying the Zmijewski and Grover models to predict bankruptcy and assess financial health. Results indicate significant variations in financial performance across companies, with some showing stability and others fluctuating between healthy and distressed states.The research identifies critical financial ratios used in performance evaluation and highlights the relevance of each method. Findings suggest that while both models are valuable, the Zmijewski model demonstrates higher accuracy (93%) compared to the Grover model (77%), making it more reliable for predicting financial distress. This study contributes to better financial management practices in the telecommunications sector, offering investors a comprehensive tool for making informed decisions and mitigating risks.